CEO Financial Education, Firm Performance, and ESG Performance of LQ45 Companies - Thomas, Mario Yohanis; Suhardianto, Novrys (Akuntansi: Jurnal Akuntansi Integratif, 2025)
Financial education that emphasizes only economic perspectives and moral hazard tends to make CEOs with financial expertise highly profit-oriented. Therefore, it is important to identify the influence of a financial education background on the financial performance of LQ45 companies, as well as the role of ESG performance in moderating this relationship. The analysis was conducted using Multiple Least Squares Regression and Moderated Regression Analysis on 166 observations indexed in LQ45 from 2017 to 2022. The results of the analysis indicate that the financial expertise of the CEO has a positive effect on financial performance, and ESG performance weakens this influence. This study's findings have practical implications, suggesting that ESG performance can serve as a governance mechanism to mitigate extreme profit orientation, allowing for the optimization of non-financial aspects such as the company's ESG performance.